Improving Breastfeeding Outcomes: A Pilot Randomized Controlled Trial of a Self-efficacy Intervention with Primiparous Mothers - McQueen, Karen A. (2009)
Breastfeeding is recommended as the optimal source of nutrition for newborns for the first 6 months of life and beyond with the addition of complementary foods. While breastfeeding initiation rates have been increasing, duration rates remain a concern as many women prematurely discontinue due to difficulties encountered rather than maternal choice. In addition, there is a sizable gap between rates of exclusive breastfeeding and current recommendations. Targeting modifiable variables that may be amenable to intervention is one strategy to improve breastfeeding outcomes. One such modifiable variable is breastfeeding self-efficacy. Although research has clearly shown that breastfeeding self-efficacy is predictive of breastfeeding duration and exclusivity, it is unknown whether it can be enhanced to improve breastfeeding outcomes. The purpose of this pilot randomized controlled trial was to examine the feasibility and compliance of a newly developed trial protocol and the acceptability of an intervention to increase breastfeeding self-efficacy in the immediate postpartum period. Secondary outcomes included determining whether there were any trends between groups related to breastfeeding self-efficacy, duration, and exclusivity. Participants included 150 primiparous mothers who were breastfeeding their healthy, full-term infants. Eligible and consenting mothers were randomized to either a control group (standard postpartum care) or an intervention group (standard postpartum care plus the self-efficacy intervention). Participants allocated to the intervention group received three individualized, self-efficacy enhancing sessions with the researcher; two sessions were conducted in hospital, and one was administered via telephone 1 week following hospital discharge. A research assistant blinded to group allocation collected outcome data at 4 and 8 weeks postpartum. The results suggested that the administration of the intervention was feasible and that there was a high degree of protocol compliance; the majority of participants reported that the intervention was beneficial. Secondary outcomes identified that there was a trend among participants in the intervention group to have improved breastfeeding outcomes, including higher rates of breastfeeding self-efficacy, duration, and exclusivity at 4 and 8 weeks postpartum. Preliminary evidence also suggested that the self-efficacy intervention may have assisted to decrease perceptions of insufficient milk supply among the intervention group participants. Overall, the findings from this pilot trial indicated that a larger trial is warranted.